Parametric study of innovative bolted shear connectors using 3D finite element modelling. (April 2021) - Hosseini, Seyedeh Maryam; Mashiri, Fidelis; Mirza, Olivia
Abstract: This paper describes an extensive numerical analysis and parametric studies conducted to evaluate the performance of shear connectors as a key component in the design of composite beams. The shear connector is essentially used to transfer shear forces across steel beams and concrete slabs in composite structures. However, conventional methods which rely mainly on the welded stud shear connector are not as efficient in terms of recycling and reusing building components. Therefore, to address the issues of deconstruction and materials reuse and to improve the structural performance of the composite beams, bolted shear connectors have been developed to replace the conventional welded stud. In order to further study their behaviour, the structural performance of the bolted shear connectors were simulated and compared with the welded studs using Abaqus software. A tridimensional numerical model was validated using previously conducted experimental tests and was used as a reference for the parametric study. Height to diameter ratio, friction coefficient of steel-concrete interface, and concrete strength were selected as the main variables for the parametric study, along with the effects of the bolt-hole clearance. The results of numerical simulation were used to develop shear stress and ductility criteria of the innovative shear connector for design rules. The results of parametric studies also showed that the load carrying capacity of composite beams using the bolted shear connectors is influenced by the bolt's height, the friction coefficient of contact surfaces and the concrete strength. Highlights: Numerical analysis and parametric studies conducted to evaluate behaviour of shear connectors. Structural performance of the bolted shear connectors was simulated and compared with welded studs. Height to diameter ratio, friction coefficient, concrete strength and bolt-hole clearance were analysed. FEM results used to develop shear stress and ductility criteria of the bolted shear connector.